Towards a Process for Migrating Legacy Systems into Microservices Architectural Style - Wolfart, Daniele; Schmeing, Ederson; Geraldino, Gustavo; Villaca, Guilherme; Paza, Diogo; Paganini, Diogo; Assunção, Wesley K. G.; da Silva, Ivonei F.; Santander, Victor F. A. (Anais da Escola Regional de Engenharia de Software (ERES), 2020)
Microservice architectural style is a paradigm to develop systems as a suite of small and autonomous services, communicating thought a lightweight protocol. Currently, the most common way of adopting microservice architectures is by the modernization of legacy monolith systems. The migration of a legacy system into a microservice architecture is not a trivial task. In addition, there is a lack of recommendation or guidelines on how to perform such process. In view of this, this paper presents a preliminary process for conducting the migration of legacy systems into microservice architectures. This process was defined by analyzing and discussing pieces of work on the topic. As result, we propose a process composed of eight steps, grouped in four phases, which we describe together with their common input and output.